Photoinduced Promiscuity of Cyclohexanone Monooxygenase for the Enantioselective Synthesis of α‐Fluoroketones. (16th November 2022) - Peng, Yongzhen; Wang, Zhiguo; Chen, Yang; Xu, Weihua; Hu, Yujing; Chen, Zhichun; Xu, Jian; Wu, Qi
Abstract: The development of mild, efficient, and enantioselective methods for preparing chiral fluorinated compounds has been a long‐standing challenge. Herein, we report a promiscuous cyclohexanone monooxygenase (CHMO) for the photoinduced synthesis of chiral α‐fluoroketones via enantioselective reductive dehalogenation of α, α‐halofluoroketones. Wild‐type CHMO from Acinetobacter sp . possesses this promiscuous ability innately; however, the yield and stereoselectivity are low. A structure‐guided rational design of CHMO improved the yield and stereoselectivity remarkably. Mechanistic studies and molecular simulations demonstrated that this photoinduced CHMO catalyzes the reductive dehalogenation via a novel electron transfer (ET)/proton transfer (PT) mechanism, distinct from that of previously reported reductases with similar promiscuity. This methodology was expanded to various substrates, and desirable chiral α‐fluoroketones were obtained in high yields (up to 99 %) and e.r. values (up to 99:1). Abstract : The photoinduced reductive dehalogenation promiscuity of cyclohexanone monooxygenase (CHMO) with a novel mechanism of ET/PT distinct from the photoinduced promiscuity of natural reductases is reported. Various highly enantioenriched α‐fluoroketones were synthesized by photoinduced reductive dehalogenation of α, α‐halofluoroketones in a process catalyzed by the rationally designed CHMO mutants.